Plato in Rabbi Shimeon bar Yohai's Cave (B. Shabbat 33b34a) the talmudic inversion of Plato's politics of philosophy - Fonrobert, Charlotte Elisheva 1965- (2007)
Thus we are told in one of the most famous narratives in talmudic literature, in its most elaborate and complex version in the Babylonian Talmud. The late ancient and early medieval rabbinic popularity of Rabbi Shimeon bar Yohai's (henceforth Rashbi) sojourn in the cave is demonstrated by the wide distribution of the motif in various rabbinic texts. It later gained additional prominence in the Jewish collective imagination to such a degree that no less than the composition of the Zohar was attributed to Rashbi; indeed, the text was considered a product of his sojourn in the cave. As is the case with other extensive narratives in the Babylonian Talmud about early rabbinic sages from the days of the Mishnah, different and most likely earlier versions of the whole or parts of this story can be found elsewhere in rabbinic literature. Others have gone about the task of carefully assembling and comparing the versions of the story, and various interpretations of it have been offered. Surely, any additional attempt at making sense of the story and decoding what the rabbinic narrators in the Babylonian Talmud sought to convey with its inclusion in the larger corpus needs to take this work into account.
Keywords: Caves; Platonism; Rabbis; Narratives; Babylonian Talmud; Civics; Allegory; Philosophy